Mechanistic Insights on Immune Activation-Driven Erectile Dysfunction: Evidence from Animal Models - Tiago T. Gonçalves; Raiana dos Anjos Moraes; Rinaldo Rodrigues dos Passos; Clinton Webb; Fernanda Priviero (Current Sexual Health Reports, 2026)
Abstract Purpose of Review Erectile dysfunction (ED) has traditionally been attributed to impaired hemodynamics and reduced nitric oxide (NO) bioavailability. This review examines current evidence supporting immune activation and inflammation as shared mechanisms contributing to ED across diverse pathological conditions. Recent Findings Experimental studies demonstrate that diabetes, hypertension, obesity, aging, nerve injury, and psychological stress are associated with activation of inflammatory pathways including NF-κB, Toll-like receptors, and the NLRP3 inflammasome. These pathways interact with oxidative stress and endothelial dysfunction to promote cytokine production, fibrosis, smooth muscle loss, and inflammatory cell death. Summary Current evidence identifies inflammatory and innate immune pathways as convergent pathogenic drivers of ED across diverse etiologies. Rather than representing passive consequences of underlying disease, these mechanisms actively contribute to vascular, neural, and structural dysfunction, perpetuating processes that promote erectile impairment. Recognizing the central role of immune-mediated dysfunction in ED may facilitate the development of novel therapeutic strategies targeting disease mechanisms rather than symptoms alone.